Puzzling hepatic tumor: Epithelioid angiomyolipoma. Issue 1 (28th January 2022) - Limaiem, Faten; Baccouch, Seifeddine; Boujelbene, Nadia; Atallah, Aziz; Hajri, Mohamed; Gabsi, Sofiène; Ben Farhat, Leila; Bouraoui, Saâdia
Abstract: Hepatic epithelioid angiomyolipomas are uncommon mesenchymal neoplasms. They are difficult to diagnose by imaging, especially when the fatty component is scant or absent. The gold standard for the diagnosis is histologic examination coupled with an immunohistochemical study. Positive HMB45 immunostaining of the myoid cells is a major diagnostic feature. Abstract : Hepatic epithelioid angiomyolipoma can create various histological appearances within an individual tumor. This heterogeneity makes the preoperative diagnosis by imaging, needle biopsy, and other techniques challenging.